Estudio contable y financiero para determinar el nivel de rentabilidad de la microempresa Shoes Sport de la provincia de Cotopaxi, cantón Latacunga. Período del 01 de enero al 31 de marzo de 2012 - Ruiz Rocha, Mayra Alejandra (2013)
The present research was realized to know the real situation of the Sport Shoes microenterprise of the Cotopaxi Province in Latacunga Canton, calculating key financial indicators such as liquidity factors, productivity, debt, among others. The main aim was to analyze the profitability to suggest improvements to administration; the research began with a description of definitions related with management, business, financial management and financial analysis. Consecutively, based on descriptive research, the data were collected from clients staff and administrative of microenterprise, by means of implementing surveys. The theoretical basis, through analysis and interpretation, allowed that the proposal for an economic-financial analysis, from institutional diagnosis based in the determination of strengths, weaknesses, opportunities and threats, then by means of applying the financial rates obtained information of the situation experienced by microenterprise, enhancing the following results liquidity rates greater than unity, profit margins of 20% and yield rates ranging from 2 points to 5 points, reflecting the activity is profitable.